Effect of Nurse Family Partnership–Based Family Empowerment on Preventive Behaviors for Type 2 Diabetes Complications Among Pandhalungan Mothers - Susi Wahyuning Asih; Ginanjar Sasmita Adi; Supriyadi Supriyadi (Health Dynamics, 2026)
Background: Diabetes mellitus (DM) is a major public health problem associated with a high risk of chronic complications. Preventing these complications requires active family involvement, particularly mothers as primary caregivers in managing family health. The Nurse Family Partnership (NFP) approach is considered relevant for strengthening family empowerment within the Pandhalungan cultural context. This study aimed to analyze the effect of implementing family empowerment among Pandhalungan mothers based on the Nurse Family Partnership (NFP) on preventive behaviors for type 2 DM complications. Methods: This study employed a quantitative cross-sectional design. The population consisted of 240 Pandhalungan mothers, with a sample of 165 respondents selected using multistage random sampling. Data were collected using structured questionnaires measuring the implementation of NFP based family empowerment and preventive behaviors for type 2 DM complications. Data were analyzed using Spearman Rank correlation and logistic regression tests. Results: There was a significant relationship between the implementation of NFP and preventive behaviors for type 2 DM complications (r = 0.612; p < 0.001). Logistic regression analysis indicated that NFP implementation was a significant predictor of preventive behavior (OR = 4.21; p < 0.001). Conclusions: The Nurse Family Partnership (NFP) based family empowerment approach provides a culturally appropriate and effective strategy for improving preventive behaviors in managing type 2 DM complications at the community level.